The image of women in Old Polish popular medical handbooks - Alicja Zdziechiewicz (Napis, 2024)
The subject of the article is an analysis of the image of a woman taking care of her mind, body and home contained in medical advice books (herbariums, e.g. Stefan Falimirz, Szymon Syreniusz, Marcin Siennik, Hieronim Spiczyński, Marcin from Urzędów, encyclopaedic compendia – Benedykt Chmielowski's Nowe Ateny [New Athens]), created in Polish in the 16th–18th centuries for a wide audience. There were also works addressed primarily to female readers (e.g. Andrzej Glaber's Aristotle-inspired Gadki o składności członków człowieczych [Considerations about disposition of the human body] of 1535; medical and cosmetic advice in Siennik and Sebestian Śleszkowski's translations of Aleksei Pedemontan's Italian Tajemnice [Secrets] of 1563; treatises on midwifery). In these, women are treated as full recipients of the text, so there is rarely an emotional or moralising tone towards them.